Two and a Half Tales of Europe: How the European Commission Narrates Peoplehood in Migration and Citizenship Policy - Johanna Hase (JCMS: Journal of Common Market Studies, 2024)
Since 2019, the European Commission has had a vice president for `promoting our European way of life', but whether a European `we' exists at all is disputed. This article investigates whether and how the Commission has constructed this `we' through narratives of peoplehood. Analysing official communications in migration and citizenship policy between 2007 and 2020, it traces three narrative elements: characters, plot and main theme. The article argues, first, that the Commission's narrative of `realizing European citizenship' creates a sense of peoplehood more than its narrative of `achieving a comprehensive migration policy' and, second, that it has largely repeated its citizenship narrative while adapting its migration narrative. The findings suggest that the Commission is a rather subtle narrator of peoplehood and call into question whether it has a clear idea of the `we' whose `way of life' it seeks to promote.
Keywords: 320; citizenship; European Commission; migration; narrative analysis; peoplehood